Gato preto: denegrindo o ensino de linguagens em uma escola do sistema prisional - Pedro Henrique Souza da Silva (2020)
The Education of Youth and Adults in penal establishments is a concern and focus of this work, which conducts analyzes based on reflections on practices of classroom in cell, experienced at the Herbert José de Souza State School, housed in two penal units from Vespasiano, in the Belo Horizonte metropolitan area: Vespasian Prison (PREVESP) and the Reference Center for the Pregnant Women Deprived of Liberty (CRGPL). I defend the importance of stimulating the adoption of Portuguese language classes in a decolonial and Afrocentric perspective in these contexts of deprivation of liberty. This proposal aims to make students recognize themselves in the studied content, so that they could perceive, in the convergence of what has been learned and their realities, tools to overcome the social condition to which they are exposed. To achieve this goal, I carried out field research, on the occasion I interviewed sixteen students from PREVESP, on the occasion I interviewed sixteen students from PREVESP, whose questions were about the school trajectory of these women; the meanings they attributed to the teaching of the Portuguese language to which they had access; and the ethnic-racial identity. I also asked them about our classroom practices, so, finally, I asked them about the relationship between Educator and students. The data collected shows the potency of the teaching perspective that I defend. Finally, I present the anthology entitled “Ninguém põe algemas nos pulsos do pensamento: a escrita literária de Educandos e Educandas da EJA em contexto prisional” [Nobody puts handcuffs on the wrists of thought: the literary writing of EJA students and students in a prison context]. This collection is composed of differents textual genres, chosen by male and female students. At the end of this work, there are a glossary, wich aims to register some of the linguistic variant used in this context, and three "didactic sequences" directed to educators who may use this material in his classes with students in resembling situation.